If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -75 + -11x = 46 Solving -75 + -11x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '75' to each side of the equation. -75 + 75 + -11x = 46 + 75 Combine like terms: -75 + 75 = 0 0 + -11x = 46 + 75 -11x = 46 + 75 Combine like terms: 46 + 75 = 121 -11x = 121 Divide each side by '-11'. x = -11 Simplifying x = -11
| 6v-4=-2(v-2) | | 8/5k-3/2k= | | K/12-1=-3 | | x^3/x^6 | | c=1075 | | (64x^5y^-4z^9)^-2/3 | | 12x+102=-66 | | 3+(2d-5)=2+(2d-4) | | (2lnx-(lnx)^2)/x | | 416/13 | | X^2-2+4x^2=18 | | 28=4x+8(x-7) | | (b*2.8)+83=39 | | 7=54.85-0.75x | | -4x-[-(7x)+2]=-14 | | 6+3(11)-(25)= | | x+3.5x=0.5+x | | 3(u+4)+4u=-2 | | -3(3w-3)=10(7-w) | | X/8=3/17 | | p-9r+3p+3r= | | 15x^2=18x | | 5z+7=5(z+4)-20 | | .666666666666666666b+5=20-b | | 6(1-4n)+8(n-2)= | | 2x-4+1=-2x+1 | | 81=n-100 | | x^6+6x-6=10 | | 6+3(11)-25= | | (r*1.2)+7.5=45 | | 9+11p-8=7p+17-4p | | 3x^2+22x-16=x |